2020
DOI: 10.1177/2374289520951924
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing US Allopathic Medical Students to Choose Pathology as a Specialty

Abstract: The SARS-CoV-2 pandemic has highlighted the crucial role of pathologists in the health care system at a time of significant decline in the number of US medical students matching to pathology residency positions. To understand this decline, a national survey of fourth-year US allopathic medical students was conducted to assess experiences, knowledge, and attitudes of pathology and factors that impact specialty choice. Participating in a separate pathology course did not increase the probability of choosing path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…A relatively acceptable proportion (50.4%) of the participants had general satisfaction with the teaching of Pathological Anatomy, with a relationship between the degree of satisfaction with the teaching and the year of study (p 0.037). This level of satisfaction is comparable to that of studies in developed countries [5,10,11]. One of the major problems with Pathological Anatomy remains its lack of visibility and its ignorance by students.…”
Section: Discussionsupporting
confidence: 71%
“…A relatively acceptable proportion (50.4%) of the participants had general satisfaction with the teaching of Pathological Anatomy, with a relationship between the degree of satisfaction with the teaching and the year of study (p 0.037). This level of satisfaction is comparable to that of studies in developed countries [5,10,11]. One of the major problems with Pathological Anatomy remains its lack of visibility and its ignorance by students.…”
Section: Discussionsupporting
confidence: 71%
“…Between 2011 and 2021, the number of US allopathic seniors matching in pathology declined from 267 (1.7% of all graduates) to 198 (1.1%), and between the years 1986 and 2020, the percentage of US Seniors matching to pathology programs ranged from a high of 2.4% to a low of 0.9%. 1 , 2 , 3 , 4 , 5 , 6 Pathology in particular matches fewer US medical graduates than other specialties. 1 , 2 , 3 , 4 , 5 , 6 There is on-going concern for maintaining an adequate number of practicing pathologists to meet the needs of the US healthcare system, and how best to plan for an optimal workforce.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 Pathology in particular matches fewer US medical graduates than other specialties. 1 , 2 , 3 , 4 , 5 , 6 There is on-going concern for maintaining an adequate number of practicing pathologists to meet the needs of the US healthcare system, and how best to plan for an optimal workforce. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Further analyses showed that higher percentages of younger students and those in the first two years of medical school are more interested in pathology than the senior medical students. The invisibility of pathology from the curriculum beyond the second year of undergraduate medical education and the lack of public knowledge about pathology was reported to may have an influence on the popularity of pathology [ 27 - 28 ]. To counter the ever-diminishing interest in pathology, many universities around the world have created post-second-year fellowships or intercalating years where students are given the opportunity to explore more courses in pathology to increase the uptake of pathology as a future career.…”
Section: Discussionmentioning
confidence: 99%